Active immunotherapy reduces NOTCH3 deposition in brain capillaries in a CADASIL mouse model - Daniel V Oliveira; Kirsten G Coupland; Wenchao Shao; Shaobo Jin; Francesca Del Gaudio; Sailan Wang; Rhys Fox; Julie W Rutten; Johan Sandin; Henrik Zetterberg; Johan Lundkvist; Saskia AJ Lesnik Oberstein; et al. (EMBO Molecular Medicine)
Abstract Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is the most common monogenic form of familial small vessel disease; no preventive or curative therapy is available. CADASIL is caused by mutations in the NOTCH3 gene, resulting in a mutated NOTCH3 receptor, with aggregation of the NOTCH3 extracellular domain (ECD) around vascular smooth muscle cells. In this study, we have developed a novel active immunization therapy specifically targeting CADASIL‐like aggregated NOTCH3 ECD. Immunizing CADASIL TgN3R182C150 mice with aggregates composed of CADASIL‐R133C mutated and wild‐type EGF1–5 repeats for a total of 4 months resulted in a marked reduction (38–48%) in NOTCH3 deposition around brain capillaries, increased microglia activation and lowered serum levels of NOTCH3 ECD. Active immunization did not impact body weight, general behavior, the number and integrity of vascular smooth muscle cells in the retina, neuronal survival, or inflammation or the renal system, suggesting that the therapy is tolerable. This is the first therapeutic study reporting a successful reduction of NOTCH3 accumulation in a CADASIL mouse model supporting further development towards clinical application for the benefit of CADASIL patients.